A novel UHPLC-ESI-MS/MS method and automatic calculation software for regiospecific analysis of triacylglycerols in natural fats and oils - Sazzad, Md Abdullah Al; Fabritius, Mikael; Boström, Pontus; Tarvainen, Marko; Kalpio, Marika; Linderborg, Kaisa M.; Kallio, Heikki; Yang, Baoru (Analytica chimica acta, 2022)
Regioisomeric analysis of triacylglycerols (TAGs) in natural oils and fats is a highly challenging task in analytical chemistry. Here we present a software (TAG Analyzer) for automatic calculation of regioisomeric composition of TAGs based on the mass spectral data from recently reported ultra-high performance liquid chromatography electrospray ionization tandem mass spectrometry (UHPLC−ESI−MS/MS) method for analyzing TAG regioisomers. The software enables fast and accurate processing of complex product ion spectra containing structurally informative diacylglycerol [M+NH4−RCO2H–NH3]+ and fatty acid ketene [RCO]+ fragment ions. Compared to manual processing, the developed software offers higher throughput with faster calculation as well as more accurate interpretation of chromatographically overlapping isobaric TAGs. The software determines results by constructing a synthetic spectrum to match the measured fragment ion spectrum, and by reporting the optimal concentrations of TAGs used to create the synthetic spectrum. This type of calculation is often extremely challenging for manual interpretation of the fragment ion spectra of isobaric TAGs with shared fragments, hence the need for automated data processing. The developed software was validated by analyzing a wide range of mixtures of regiopure TAG reference compounds of known composition and a commercial olive oil sample. Additionally, the method was also applied for regiospecific analysis of TAGs in human milk as an example of natural fats and oils with a highly complex TAG profile. The results indicate that the software is capable of resolving regioisomeric composition of natural TAGs even of the most complex composition. This novel calculation software combined with our existing UHPLC-ESI-MS/MS method form a highly efficient tool for regioisomeric analysis of TAGs in natural fats and oils. [Display omitted] •Analysis of TAG regioisomers in fats and oils is a highly challenging task.•A UHPLC-MS/MS method was reported previously for regioisomeric analysis of TAGs.•A software was created for automatic data processing and calculation.•The software was applied for analysis of olive oil and human milk TAG regioisomers.